The Relation of Hormonal Contraception Use With Obesity in Women of Childbearing Age (WUS) of Public Health Insurance Participants In The Lamongan Clinic - Wasiah, Asyaul (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Obesity is caused by several factors, one of them is the use of contraception in particular the use of hormonal contraceptives that its use can cause various side effects such as changes in body weight-acceptor. The research aims to determine the relation of hormonal contraception use with obesity in women of childbearing age (WUS) of public health insurance participants in the Lamongan clinic. This study is an Observational Analytics with cross-sectional. The total sample of 77 respondents. The respondents who use hormonal contraception are 49 respondents while the respondents who did not use contraception are 28 respondents. The respondents who use hormonal contraception and were obese are 22 respondents. Conclusion: The type of contraception most widely used by women of childbearing age is hormonal contraceptives and there is no relationship between the use of contraception with obesity in women of childbearing age at Lamongan clinic.